The Spleen Revisited: An Overview on Magnetic Resonance Imaging - João Palas; António P. Matos; Miguel Ramalho (Radiology Research and Practice)
Despite being well visualized by different cross-sectional imaging techniques, the spleen is many times overlooked during the abdominal examination. The major reason is the low frequency of splenic abnormalities, the majority consisting of incidental findings. There has been a steady increase in the number of performed abdominal magnetic resonance imaging (MRI) studies; therefore, it is important to be familiar to the major MRI characteristics of disease processes involving the spleen, in order to interpret the findings correctly, reaching whenever possible the appropriate diagnosis. The spleen may be involved in several pathologic conditions like congenital diseases, trauma, inflammation, vascular disorders and hematologic disorders, benign and malignant tumors, and other disease processes that focally or diffusely affect the spleen. This paper presents a description and representative MRI images for many of these disorders.